PENINGKATAN PELAYANAN JASA KONSULTAN LINGKUNGAN HIDUP DENGAN PENGEMBANGAN WEBSITE CV FAHMI JAYA - Yulindawati Yulindawati; Ita Arfyanti (Jurnal Ilmiah Matrik, 2021)
Research on the improvement of environmental consulting services with the development of the CV website. Fahmi Jaya is a research to make it easier for the public to obtain complete and up-to-date information because information is felt to be very important in making decisions and in achieving goals. In addition to obtaining complete and up-to-date information, the website can also send and publish information to the wider community online. The system development method used in this research is the System Development Life Cycle (SDLC) method, or better known as the system development life cycle in system engineering and software engineering, is the process of making and changing systems and the models and methodologies used to develop these systems. The results of the research are expected that this system can publish its activities for more recent information so that the public can find out the activities that have been carried out, the ease of information about CV FAHMI JAYA.